Functional performance and muscular strength in symptomatic female carriers of Duchenne muscular dystrophy - SILVA, Thiago Henrique da; ANEQUINI, Isabela Pessa; FÁVERO, Francis Meire; VOOS, Mariana Callil; OLIVEIRA, Acary Souza Bulle; TELLES, Juliana Aparecida Rhein; CAROMANO, Fátima Aparecida (Arquivos de Neuro-Psiquiatria, 2020)
Duchenne muscular dystrophy (DMD) usually affects men. However, women are also affected in rare instances. Approximately 8% of female DMD carriers have muscle weakness and cardiomyopathy. The early identification of functional and motor impairments can support clinical decision making. Objective: To investigate the motor and functional impairments of 10 female patients with dystrophinopathy diagnosed with clinical, pathological, genetic and immunohistochemical studies. Methods: A descriptive study of a sample of symptomatic female carriers of DMD mutations. The studied variables were muscular strength and functional performance. Results: The prevalence was 10/118 (8.4%) symptomatic female carriers. Deletions were found in seven patients. The age of onset of symptoms in female carriers of DMD was quite variable. Pseudohypertrophy of calf muscles, muscular weakness, compensatory movements and longer timed performance on functional tasks were observed in most of the cases. Differently from males with DMD, seven female patients showed asymmetrical muscular weakness. The asymmetric presentation of muscle weakness was frequent and affected posture and functionality in some cases. The functional performance presents greater number of compensatory movements. Time of execution of activities was not a good biomarker of functionality for this population, because it does not change in the same proportion as the number of movement compensations. Conclusion: Clinical manifestation of asymmetrical muscle weakness and compensatory movements, or both can be found in female carriers of DMD mutations, which can adversely affect posture and functional performance of these patients.
Keywords: Duchenne muscular dystrophy; motor activity; muscle strength; female